Periostin: An Emerging Molecule With a Potential Role in Spinal Degenerative Diseases - Zhu, Daxue; Zhou, Wupin; Wang, Zhen; Wang, Yidian; Liu, Mingqiang; Zhang, Guangzhi; Guo, Xudong; Kang, Xuewen (Frontiers in Medicine, 2021)
Periostin, an extracellular matrix protein, is widely expressed in a variety of tissues and cells. It has many biological functions and is related to many diseases: for example, it promotes cell proliferation and differentiation in osteoblasts, which are closely related to osteoporosis, and mediates cell senescence and apoptosis in chondrocytes, which are involved in osteoarthritis. Furthermore, it also plays an important role in mediating inflammation and reconstruction during bronchial asthma, as well as in promoting bone development, reconstruction, repair, and strength. Therefore, periostin has been explored as a potential biomarker for various diseases. Recently, periostin has also been found to be expressed in intervertebral disc cells as a component of the intervertebral extracellular matrix, and to play a crucial role in the maintenance and degeneration of intervertebral discs. This article reviews the biological role of periostin in bone marrow-derived mesenchymal stem cells, osteoblasts, osteoclasts, chondrocytes, and annulus fibrosus and nucleus pulposus cells, which are closely related to spinal degenerative diseases. The study of its pathophysiological effects is of great significance for the diagnosis and treatment of spinal degeneration, although additional studies are needed.